DEVALUATION AND DAMAGES. - Coon, S. J. (The Accounting Review, 1935)
Abstract The article discusses the right to devaluation and damages. The Supreme Court of the United States, in its decision in Perry versus the United States, handed down February 18, 1935, holds that the government did not have the right to repudiate its promise to the holder of a liberty bond to pay in dollars of 25.8 grains of gold as fine. The court holds that the owner of the bond is not entitled to enrichment. He is entitled only to damages. He is denied damages by this decision because he does not possess the legal right to use gold, and because he is denied the right to sue in the Court of Claims. But the question of damages is very important because these rights might sometime be restored. Changes in the price level, as shown by index numbers, are only a generalization. As far as any individual owner of dollars is concerned, a change in their purchasing power depends upon the changes in prices of the particular things he purchases. Individual prices may he higher or lower or remain the same as before devaluation, and in order to be actually damaged the identical thing purchased must be higher in price.